The Implementation of Muwashofat Tarbiyah in the Formation of Character in Darul Azhar Islamic Boarding School - Ulantika, Bunga; Nasution, Wahyudin Nur (DAYAH: Journal of Islamic Education, 2024)
Muwashofat Tarbiyah is 10 Muslim characteristics proposed by Hasan AlBana, this character must be owned by every Muslim so as to make them a Muslim with Islamic character. Muwashofat Tarbiyah can be applied in every educational institution in order to create students who have Islamic character. this research uses a qualitative method with a field research approach that tends to be descriptive and naturalistic. collecting research data by conducting observations at Yayaysan Darul Azhar Sejahter which includes SMPS IT Darul Azhar and MAS Darul Azhar. As well as conducting interviews with foundation coaches, principals, teachers and students and collecting documentation. Data analysis used is in line with the opinion of Miles and Huberman with data reduction techniques, data presentation and conclusion drawing. The application of Muwashofat Tarbiyah can be a solution in times of moral decline and the character of the nation's children, thus making every learner a human being who has good characteristics.  holding fast to Aqidah, always worshiping Allah, having praiseworthy morals, having a strong and tough physique, having broad and global insights, and being able to fight bad desires, being able to manage time so that they are able to organize every business in an orderly manner, and being independent of themselves, so that they can benefit themselves and the surrounding community.